Bioequivalence and Relative Bioavailability Studies to Assess a New Acalabrutinib Formulation That Enables Coadministration With Proton‐Pump Inhibitors. Issue 11 (27th August 2022) - Sharma, Shringi; Pepin, Xavier; Burri, Harini; Zheng, Lianqing; Kuptsova‐Clarkson, Nataliya; de Jong, Anouk; Yu, Ting; MacArthur, Holly L.; Majewski, Michal; Byrd, John C.; Furman, Richard R.; Ware, Joseph A.; et al.
Abstract: Acalabrutinib is a Bruton tyrosine kinase (BTK) inhibitor approved to treat adults with chronic lymphocytic leukemia, small lymphocytic lymphoma, or previously treated mantle cell lymphoma. As the bioavailability of the acalabrutinib capsule (AC) depends on gastric pH for solubility and is impaired by acid‐suppressing therapies, coadministration with proton‐pump inhibitors (PPIs) is not recommended. Three studies in healthy subjects (N = 30, N = 66, N = 20) evaluated the pharmacokinetics (PKs), pharmacodynamics (PDs), safety, and tolerability of acalabrutinib maleate tablet (AT) formulated with pH‐independent release. Subjects were administered AT or AC (orally, fasted state), AT in a fed state, or AT in the presence of a PPI, and AT or AC via nasogastric (NG) route. Acalabrutinib exposures (geometric mean [% coefficient of variation, CV]) were comparable for AT versus AC (AUCinf 567.8 ng h/mL [36.9] vs 572.2 ng h/mL [38.2], Cmax 537.2 ng/mL [42.6] vs 535.7 ng/mL [58.4], respectively); similar results were observed for acalabrutinib's active metabolite (ACP‐5862) and for AT‐NG versus AC‐NG. The geometric mean Cmax for acalabrutinib was lower when AT was administered in the fed versus the fasted state (Cmax 255.6 ng/mL [%CV, 46.5] vs 504.9 ng/mL [49.9]); AUCs were similar. For AT + PPI, geometric mean Cmax was lower (371.9 ng/mL [%CV, 81.4] vs 504.9 ng/mL [49.9]) and AUCinf was higher (AUCinf 694.1 ng h/mL [39.7] vs 559.5 ng h/mL [34.6]) than AT alone. AT and AC were similar in BTK occupancy. Most adverse events were mild with no new safety concerns. Acalabrutinib formulations were comparable and AT could be coadministered with PPIs, food, or via NG tube without affecting the PKs or PDs.